A cross sectional study on household dependence on well water, source of contamination and well protection measures adopted by an urban and rural population in Kollam, Kerala - Binu, Jeffy; Salam, Halma; A., Jibina K.; Fazil, Fathahiya; T., Hasnath K.; S., Greeshma (International Journal Of Community Medicine And Public Health, 2021)
Background: Wells are a common ground water source readily explored to meet community water requirement. Open wells of Kerala have the problem of bacterial contamination, which causes diarrhea diseases especially in children. Close proximity of well to septic tank, waste pit and cattle shed can be considered as a leading cause of contamination of water. The present study had gone into the details of dependence of dug well, possible source of contamination and protective measures taken for drinking water safely by various households in both urban and rural population. Methods: Cross sectional study design applied in order to address the objectives of the study. Using systematic random sampling techniques 80 households were selected from urban and rural areas. Pretested interview schedule were used as the data collection tool. Results: 100% of households are depending on dug well for all their use like drinking, cooking, cleaning etc. 95% households treat water and among them 93.4% boil water before drinking. 40% of houses followed well protection measures. Significant association was found between urban and rural set-up in the distance of well from septic tank (p value is 0.004<0.01). There is statistically significant association in frequency of chlorination in urban and rural population (p value is 0.015<0.05). Occurrence of diarrhea was found to be nil in past two weeks from the time of data collection among under-fives. Conclusions: Disease like diarrhea can be prevented in under-fives by following well protection measures and boiling water before drinking in both urban and rural areas.